Assessment of the phytochemical, antioxidant and antibacterial activities of Heteromorpha arborescens (Spreng.) Cham & Schltdl. leaf extracts - Abifarin, Taiwo Oluwafunmilola (F1000Res, 2020)
Background: Heteromorpha arborescens (Spreng.) Cham. and Schltdl (Apiaceae) is widely used traditionally for the treatment of a wide range of diseases in Southern and Eastern Africa. Although previous studies have reported the biological activities of hexane, ethyl acetate and methanol extracts of H. arborescens leaves, there is no scientific information on the phytochemical contents, antioxidant and antibacterial activities of acetone, ethanol, aqueous and blanched extracts. This study is therefore aimed to investigate and compare the phytochemical contents, antioxidant and antibacterial activities of acetone, ethanol, aqueous and blanched extracts of H. arborescens leaves. Methods: Phytochemical analysis for the total phenolic, flavonoid, proanthocyanidin, alkaloid and saponin contents of all the fractions were determined by spectroscopic methods, while the free radical scavenging potential of the extracts were evaluated using DPPH, ABTS radical scavenging and total antioxidant capacity assays. Micro dilution method was used to determine the Minimum Inhibitory Concentrations (MIC) of H. arborescens leaf extracts against Bacillus pumilus, Staphylococcus epidermidis, Staphylococcus aureus, Escherichia coli and Klebsiella pneumoniae. Results: Total phenol content of the extracts ranged between 15.10 mg GAE/g- 42.50 mg GAE/g, proanthocyanidin was 459-8402.1 mg QE/g, and flavonoid content of 109.24-235.79 mg QE/g. In addition, alkaloids (5.59%) and saponins (23.33%) were present in significant amounts. Based on the IC (50) values, the ethanol extract exhibited the highest total antioxidant activity (0.013 mg/mL) with highest inhibition against DPPH and ABTS radicals (0.06 and 0.049 mg/mL respectively). Considerable antibacterial activities were observed in the acetone, ethanol and blanched extracts with MIC values ranging from 1.563-12.5 mg/mL; however, the aqueous extract was inactive against all the bacteria strains. Conclusion: The study suggests that H. arborescens leaves could be a valuable source of bioactive compounds. Although the blanching process significantly decreased polyphenolic contents and antioxidant activities of the extracts, it increased the antibacterial compounds.